Usability Evaluation of the SiCanTiK Website at SMKN 3 Kota Kediri Using the System Usability Scale and USE Questionnaire - Lukman, Muhammad Abi; Daniati, Erna; Wardani, Anita Sari (Information Technology and Science (ITScience), 2025)
The rapid advancement of information technology has driven the transformation of learning systems, especially in vocational education. SMKN 3 Kota Kediri has developed an e-learning platform called SiCantik (Sistem Informasi Canggih Terintegrasi dan Kolaboratif) to support the online learning process. However, despite its potential, the platform faces several usability issues such as difficulties in navigating features and accessing learning content, which may hinder learning outcomes. This study aims to analyze the usability level of the SiCantik website using the System Usability Scale (SUS) and the USE Questionnaire. A descriptive quantitative method was employed, and data were collected from 100 respondents through online questionnaires. Validity and reliability testing were conducted to ensure the accuracy of the instruments. The SUS results showed an average score of 61.8, which falls into the “Poor” category, indicating that the platform's usability is marginally acceptable. Meanwhile, the USE Questionnaire results produced an average usability percentage of 65.5%, which is categorized as “Feasible.” Among the four evaluated dimensions, Ease of Use had the highest score (68.5%), while Ease of Learning had the lowest (63.2%). These results imply that while users generally find the system usable, improvements are still needed, particularly in user guidance and system intuitiveness. This research provides valuable input for system developers and stakeholders to improve the user experience of educational platforms. Further research is recommended to evaluate the technical performance and long-term user engagement of the system.